Individual radiosensitivity: a key issue in radiation protection. (1st January 2013) - Bourguignon, Michel; Foray, N.; Colin, C.; Pauwels, Ernest
Immunofluorescence that permits the detection of nuclear targets specific to DNA damage signalling and repair have completely renewed the approach of individual radiosensitivity. It is a concern in radiotherapy in which radiosensitivity is responsible for the development of adverse side-effects in normal tissues in absence of any mistake in the dose delivery. Furthermore, individual radiosensitivity at low-dose has been recently demonstrated in human mammary epithelium exposed ex vivo in the conditions of mammographic screening. Although these results do not demonstrate directly the existence of mutagenesis, they indicate a possible link between cancer proneness and radiosensitivity. Hence, individual radiosensitivity is a real concern for public health since 5-15% of the population may be concerned and radiosensitive individuals generally show higher cancer risk than the rest of the population. Thus, individual radiosensitivity is a key issue to be addressed in future recommendations of the radioprotection system.